Nanodiamond-based nanostructures for coupling nitrogen-vacancy centres to metal nanoparticles and semiconductor quantum dots - Jianxiao Gong; Nat Steinsultz; Min Ouyang (Nature Communications, 2016)
The coupling of nitrogen-vacancy centres with plasmonic and photonic nanostructures is usually studied by top-down preparation. Here, Gong et al. use a bottom-up approach to grow metallic and semiconducting nanoparticles on nanodiamonds, controlling the nanoparticle coverage, size and composition.